Religiusity of Indigenous Communities in Indonesia - Yunus, Badruzzaman M; Nurhasanah, Siti; Irwansyah, Shindu; Saepulah; Muhyiddin, Asep (International Journal of Psychosocial Rehabilitation, 2020)
This study is intended to reveal and examine the religiosity of indigenous community in Cireundeu village in Indonesia, which is expressed in the symbols of their daily lives. This research applied ethnographic method in a phenomenological perspective using a qualitative approach. The indigenous community of Cireundeu have tendency to make “religion” as “the ultimate concern”. They regard religion a fundamental philosophy in their lives where almost all their activities are based on religious values.